Challenges and treatment outcome of patients with Kaposiform hemangioendothelioma: a retrospective single center experience - Nihal Hussien Aly; Amr AbdelHamid AbouZeid; Shaimaa Abdelsattar Mohammad; Saleh Abdulrazaq Alashban; Iman Ahmed Ragab (Egyptian Pediatric Association Gazette)
Abstract Background Kaposiform hemangioendothelioma (KHE) is a rare vascular tumor with variable treatment approaches. We aimed to identify the outcome of patients with KHE treated at our center, timing for hematological response, and the risk factors for refractoriness to treatment. Methods A retrospective review of patients with diagnosis of KHE with thrombocytopenia was done. Thrombocytopenia was divided into mild, moderate, severe, and very severe, with severity score given to patients according to symptoms and complications. Digital photography and conventional pre-contrast MRI and dynamic postcontrast sequences for cases at presentation were included. Treatment protocol included first line with oral or intravenous steroid with weekly vincristine then sirolimus used as second line for refractory cases due to unavailability of the solution form in our center being in low to middle income country. Treatment response was mainly identified by changing to less severe stage in platelet count with clinical response. Results Ten patients with KHE were included. The most common site was the extremities (five patients). The percentage of involved body surface area ranged from 2 to 15%. Life threatening events were present in five patients; six patients (60%) had successful treatment response to first line treatment with mean duration to normalization of platelet was 2 to 4 weeks. The four patients who failed steroids/vincristine were treated with second line sirolimus with complete hematological response in two patients. Conclusion Although KHE is aggressive neoplasm, good response to first and second lines of treatment were obtained in the majority of patients.